The detrimental impacts of smart technology device overuse among school students in Kuwait: a cross-sectional survey - Ali Jasem Buabbas; Madawi Anwar Al-Mass; Basma Awad Al-Tawari; Mohammad Abbas Buabbas (BMC, 2020)
Abstract Background Children and adolescents are becoming the most prolific users of smart technology (ST) devices due to the numerous advantages presented by these devices. However, the overuse of ST devices can have detrimental impacts on health. Therefore, the aim of this study was to investigate the pattern of ST device use among school students in Kuwait and the possible associated health problems. Methods This cross-sectional survey used a pretested questionnaire to collect data from students of different educational levels within the governmental sector: primary, secondary and high school. Chi-square tests were applied to find associations or significant differences between the categorical variables, in which p < 0.05 was considered statistically significant. Results This study included 3015 students, of whom 53.6% were female. The sample had an equal distribution of primary (33.8%), secondary (32.4%) and high school students (33.8%). Almost all of the participants (99.7%) owned a ST device, chiefly smartphones (87.7%). Most of the students used ST devices for > 4 total hours per day on average, which is categorised as "overuse". Among those overusing ST devices, the symptoms most commonly experienced included headaches (35.0%), sleep disturbances (36.6%) and neck/shoulder pain (37.7%). Students who used ST devices for < 1 h per session experienced eye-related problems. Moreover, students who played sports on a regular basis were more likely to spend less time per session on ST devices. The prolonged use of ST devices was associated with higher reporting of seizures, eye squints and transient vision loss. Conclusion The overuse of ST devices per day and per session by school-aged children has the potential to have a detrimental impact on their health, as has been noticed among students in Kuwait. Healthcare professionals, school authorities and parents could use these results to plan strategies to change ST device use behaviours among schoolchildren.